2019
DOI: 10.3390/nano9040616
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thickness of Molybdenum Nano-Interlayer on Cohesion between Molybdenum/Titanium Multilayer Film and Silicon Substrate

Abstract: Titanium (Ti) film has been used as a hydrogen storage material. The effect of the thickness of a molybdenum (Mo) nano-interlayer on the cohesive strength between a Mo/Ti multilayer film and a single crystal silicon (Si) substrate was investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), and nano-indenter. Four groups of Si/Mo/Ti multilayer films with different thicknesses of Mo and Ti films were fabricated. The XRD results showed that the introduction of the Mo layer suppressed the chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…However, Sadek et al (2019) reported that the oxide phase of Co metal was observed at 2 = 36.80°, 59.30°, dan 65.20° [24]. On the other hand, the diffraction peaks for Mo metal were reported at 2θ = 57.76° and 72.87° [25].…”
Section: Catalysts Characteristicsmentioning
confidence: 98%
“…However, Sadek et al (2019) reported that the oxide phase of Co metal was observed at 2 = 36.80°, 59.30°, dan 65.20° [24]. On the other hand, the diffraction peaks for Mo metal were reported at 2θ = 57.76° and 72.87° [25].…”
Section: Catalysts Characteristicsmentioning
confidence: 98%
“…The stress measured by the curvature method are residual compressive stress, which is consistent with the SAW method. There is a slight difference in the SAW determination results between [100] and [110] direction, which might be caused by the differences in thermal expansion coefficients and elastic modulus due to the different atomic arrangement in different crystallographic orientations of the anisotropic Si substrate [33,36,37]. All three sets of data show the same trend, and the residual compressive stress in the SiO 2 film decreases as the film thickness increases, proving the feasibility of the SAW method [38].…”
Section: Resultsmentioning
confidence: 86%
“…The major compounds of key interest were studied, including AlGaN [1], Cu NWs [2], photonic crystal fibers [3], LiNbO 3 [4], Au nanoparticles [5], Al 2 O 3 /Tm 2 O 3 [6], Ge-DLC [7], Mo/Ti [8], ZnTe:Cu [9], Ge–Sb–Te [10], noble metal nanoparticles [11], collagen/Zn 2+ -substituted calcium phosphates [12], TiO 2 [13], Si-DLC [14], SHG in ZnO nanofilms [15], Cu 2 Mg x Zn 1−x SnS 4 [16], ethylene vinyl acetate (EVA) matrices [17], and LIPSS [18].…”
mentioning
confidence: 99%